2016
DOI: 10.1080/15332640.2015.1113152
|View full text |Cite
|
Sign up to set email alerts
|

Perceived racial discrimination, heavy episodic drinking, and alcohol abstinence among African American and White college students

Abstract: Previous research has demonstrated that white college students are more likely to drink alcohol at a greater frequency and quantity compared to their African American counterparts. Examining race-related factors that structure alcohol use among college students remains an important area of research. This study specifically examines perceived discrimination and its association with both heavy episodic drinking (HED) and alcohol abstinence among college students. Items that measured perceived racial discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…29,30 Thus, an intersectional framework allows for exploring the compounding effects of race, gender, and sexual identity that may affect alcohol consumption. 31,32 Research has shown that Black college students tend to drink to cope (drinking to reduce stress and negative affect) [33][34][35] which rapidly escalates during the transition from adolescence to young adulthood and can lead to excessive alcohol use and alcohol-related problems into adulthood. 36 Sexual orientation further complicates the alcohol behaviors of college students.…”
Section: Intersecting Identities and Alcohol Usementioning
confidence: 99%
“…29,30 Thus, an intersectional framework allows for exploring the compounding effects of race, gender, and sexual identity that may affect alcohol consumption. 31,32 Research has shown that Black college students tend to drink to cope (drinking to reduce stress and negative affect) [33][34][35] which rapidly escalates during the transition from adolescence to young adulthood and can lead to excessive alcohol use and alcohol-related problems into adulthood. 36 Sexual orientation further complicates the alcohol behaviors of college students.…”
Section: Intersecting Identities and Alcohol Usementioning
confidence: 99%
“…Racial discrimination (discrimination) has been recognized as a risk factor for problematic alcohol use (i.e., frequency and pattern of alcohol use that entails negative physical, social, and psychological consequences; Gorka, Ali, & Duaghters, 2012) in African American (AA) emerging adulthoods (Gerrard et al, 2012;Hurd, Varner, Caldwell, & Zimmerman, 2014;Stevens-Watkins & Rostosky, 2010;Stock, Gibbons, Walsh, & Gerrard, 2011;Stock et al, 2013;Wade & Peralta, 2016). Although researchers have consistently found that AA adolescents consume less alcohol than their White peers (Bachman, Wadsworth, O'Malley, Johnston, & Schulenberg, 2013), researchers have also found that AA emerging adults exceed their White counterparts in rates of alcohol-related problems (Clark, Corneille, & Coman, 2013).…”
mentioning
confidence: 99%
“…Individuals who chose the option of identifying as belonging to more than one race were coded as multiracial (see Table 1). The decision to examine differences in ethnic identity by racial group, rather than ethnic group, is also consistent with prior research (e.g., Bracey, Bámaca, & Umaña-Taylor, 2004;Smith & Silva, 2011;Wade & Peralta, 2017). This allowed for the exploration of how non-White college students' drinking behaviors are related to ethnic identity, which would have been otherwise obscured in the predominately White sample.…”
Section: Samplementioning
confidence: 70%